Augmented mapping and analysis of pancreatic fat by quantitative MRI - Triay Bagur, A (2022)
The incidence of pancreas pathology is rising rapidly. While early detection is critical, these are often "silent" conditions that only become symptomatic at a late stage, when they may already be untreatable. Incidental findings, where the target organ is near the pancreas, offer a way to detect pancreas pathology in time. Pancreatic ectopic fat is an early manifestation of disease, and evaluation using MRI is receiving increasing interest. However, it is challenged by the remarkable variability of the pancreas across individuals and its physiological complexity. Quantitative Magnetic Resonance Imaging (MRI) has shown potential for imaging biomarker development, including Proton Density Fat Fraction (PDFF) and T1, though some challenges remain.